The Development of E-book Based on Realistic Mathematics Education (PMR) Approach to Improve Mathematical Communication Skills in Class VIII Junior High School Students - Wan Putri Tania; Nurhasanah Siregar (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This study aims to obtain an e-book based on the Realistic Mathematics Education (PMR) approach that is valid, practical, and effective so that it can improve students' mathematical communication skills on the Two-Variable Linear Equation System (SPLDV) material. This type of research is Research and Development (R&D) using the ADDIE model which consists of five stages, namely analyze, design, development, implementation, and evaluation. The research instruments used were questionnaire and instrument validation sheets, lesson plans validation sheets, e-book validation sheets, mathematical communication skills tests, and student and teacher response questionnaires to e-books. Based on the research, the results of the RPP validation were obtained with a percentage of 88% (very valid), e-book validation with a percentage of 82% for material, and 90% for media with a very valid category. The results of student responses with the percentage of the practicality of 86% (very practical) and the teacher's response questionnaire with the percentage of the practicality of 86% (very practical). The results obtained by meeting the effective criteria with a classical student learning completeness score of 96%, more than 65% of students achieving 75% of the learning objectives for each indicator, and the learning time is the same as ordinary learning in field trials and student responses are good to the e-book provided. developed. Through the Gain test, it is seen that students' mathematical communication skills using e-books based on the PMR approach have increased by 0.7, meaning that they are in the high category. Keywords: e-book, realistic mathematics education, mathematical communication.